Efektivitas Penyuluhan Pertanian Dalam Pengembangan Usaha Tani Tembakau (Studi Kasus : Desa Prupuh Kecamatan Panceng Kabupaten Gresik) - Mubarok, Ficky Auliyyaul Ikhsan; Djazuli, Raden Achmad (CV.ITTC INDONESIA, 2024)
Agricultural extension refers to the dissemination of knowledge from an instructor to those involved in the agricultural industry. The research was conducted in Prupuh Village, Panceng District, Gresik Regency, which has 14 hamlets. Agricultural production in this location is still relatively poor. Low agricultural productivity is caused by the low ability of farmers to apply agricultural technology and innovation. As a result, an agricultural extension program was implemented, with a special focus on tobacco production. This research was conducted to assess the effectiveness of agricultural extension services. The sampling technique used was purposive sampling, namely selecting 3 farmers as research respondents from a total of 14 hamlets, resulting in a total of 42 respondents. Research findings show that the implementation of extension programs involves two different processes: farmer participation in the extension process and farmer involvement in decision making with an average score of 2.845. Regarding the implementation of extension programs, currently there are 8 programs with an average score of 2.899. this indicates that counseling can be considered successful because the score is above the threshold.